Gathering the Threads - Woodsmall, Cindy (New York : WaterBrook, 2017)
"After months away in the Englisch world, Ariana Brenneman is overjoyed to be in the Old Order Amish home where she was raised. Yet her excitement is mixed with an unexpected apprehension as she reconciles all she's learned from her biological parents with the uncompromising teachings of her Plain community. Although her childhood friend, ex-Amish Quill Schlabach, hopes to help her navigate her new role amongst her people, Ariana's Daed doesn't understand why his sweet daughter is suddenly questioning his authority"--Amazon.com.
Keywords: Infants switched at birth -- Fiction; Amish -- Fiction; Fathers and daughters -- Fiction; Families -- Fiction; Domestic fiction; Christian fiction